THE PHILOSOPHY OF OCEANIC VERSES OF THE QUR’AN AND ITS RELEVANCE TO INDONESIAN CONTEXT - Agus S Djamil; Mulyadhi Kartanegara (Analisa: Journal of Social Science and Religion, 2017)
The Qur’an is not merely a transcendental or spiritual Holy Scripture, but it also establishes itself as the full assurance and un-doubtful scripture that gives guidance and its explanation thereof. Oceanic versesare certain selected ayats or verses of the Qur’an that contain words of ‘ocean’ and ‘sea’ in several terms such as bahr, bahri, bahru, bihar, bahrayn, bahran, abhur, and bahiratun. These verses have been examined in classical and contemporary studies by putting together earlier exegeses with modern scientific records and field observations but not in terms of established theories, nor through socio-economic paralellistic approach. This paper focuses on the semantics and ontology of oceanic verses and paralellistic approach as they were revealed and found in 42 verses in the Qur’an. Keywords in those verses were studied to enable us to build and lead us to practical benefit in science, technology and methodology. The interpretation of Qur’anic verses pertaining to ocean phenomena offers an alternative interpretation on several relevant issues, including fire/energy within ocean; two oceans that do not mingle; the darkness of the ocean deep; the ocean boundaries; the layers of the ocean; and the abundance wealth and benefits from ocean for mankind. Indonesia is blessed with the ability to combine the Qur’an containing plenty of oceanic guidance and its geographical position as the most strategic archipelago on earth. Cascading the oceanic verses into daily da’wah and weekly Friday sermon is a necessary means to reap the ontological benefits of the blessing Qur’an and of dwelling in the largest marine continent of Indonesia.